2013
DOI: 10.3329/icpj.v2i10.16408
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of fucoidan from Sargassum wightii against the chosen human bacterial pathogens

Abstract: The present study was aimed to evaluate the antibacterial capability of fucoidan from Sargassum wightii against the chosen human bacterial pathogens. The major chemical constituents of the extracted fucoidan were analyzed by biochemical methods. It showed that the extracted fucoidan contains 52.86 ± 0.64% of fucose and 29.26 ± 0.83% of sulphate. The antibacterial efficacy was performed by agar well diffusion, minimum inhibitory concentration (MIC) and minimum inhibitory concentration (MBC) method. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Based on the results of antibacterial susceptibility test on fucoidan and alginic acid in the present study, fucoidan (0.50 mol/L) and alginic acid (0.50 mol/L) were observed to have antibacterial property against Gram-positive bacteria S. aureus (inhibition zone of 7.43±0.17 mm and 7.45±0.14 mm, respectively). This is in agreement with the study of Marudhupandi and Kumar that showed the inhibition of fucoidan against Vibrio cholerae (18.6±0.32 mm) and Salmonella typhi (8.6±0.26 mm) [23].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of antibacterial susceptibility test on fucoidan and alginic acid in the present study, fucoidan (0.50 mol/L) and alginic acid (0.50 mol/L) were observed to have antibacterial property against Gram-positive bacteria S. aureus (inhibition zone of 7.43±0.17 mm and 7.45±0.14 mm, respectively). This is in agreement with the study of Marudhupandi and Kumar that showed the inhibition of fucoidan against Vibrio cholerae (18.6±0.32 mm) and Salmonella typhi (8.6±0.26 mm) [23].…”
Section: Discussionsupporting
confidence: 93%
“…Another very interesting group of polysaccharides obtained from algae with a demonstrated antimicrobial potential is Fucoidans (polysaccharides from Phaeophyta). Among the most important properties of these polysaccharides are the following: anticoagulant, antithrombotic, antiviral, antitumor, immunomodulatory, antioxidant, and anti-inflammatory (Li, Lu, Wei, & Zhao, 2008;Marudhupandi & Kumar, 2013). According to the studies of De Jesus Raposo, Bernardo de Morais, and Santos Costa de Morais (2015), sulphated polysaccharides from seaweeds (among them alginates, fucoidans and laminaran) have demonstrated to be effective against E. coli and Staphylococcus aureus (Chaetomorpha aerea, 50 mg/mL of extract).…”
Section: Carbohydratesmentioning
confidence: 99%
“…As the main bioactive components in marine algae, sulfated polysaccharides, particularly their bacteriostatic or bactericidal activity, have attracted attention [4]. In brown algae, the sulfated polysaccharides from Laminaria japonica and Sargassum swartzii can inhibit Gram-negative and -positive bacteria including E. coli, Vibrio cholera, Salmonella typhi, and Staphylococcus aureus [5,6]. The sulfated polysaccharides from green algae (Chaetomorpha aerea) and microalgae (Porphyridium cruentum) also display inhibitory effect on S. aureus and Salmonella enteritidis, respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%